Patient Satisfaction and its Socio-Demographic Correlates in Zainoel Abidin Hospital, Indonesia: A Cross-Sectional Study - Azharuddin Azharuddin; Novi Reandy Sasmita; Ghalieb Mutig Idroes; Rusdi Andid; Raihan Raihan; Tuti Fadlilah; Nanda Earlia; Taufik Ridwan; Ira Maya; Farnida Farnida; Rinaldi Idroes (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2023)
Patient satisfaction based on a patient’s opinion is the main criterion and can be one of the best ways to measure the quality of healthcare services. In this study, we determined patient satisfaction in hospital healthcare services at Zainal Abidin Hospital (RSUZA) and the socio-demographic factors associated with patient satisfaction. We conducted a cross sectional study at RSUZA. To recruit participants, purposive sampling and accidental sampling are used in this study. The binomial proportion is used to determine the total number of respondents. The questionnaire was tested for was performed. The chi-square test of independence was used to analyze the difference in each answer on each variable. The Kendall tau correlation was used to explore the correlation between social demographic variables and the total patient satisfaction value. The questionnaire used in this study is valid (p < 0.000) and reliable (Cronbach’s Alpha = 0.785). Of 904 respondents, 809 respondents (89.5%) were satisfied with the services provided by RSUZA. There was no difference on respondent in the gender category (p = 0.309), the age category (p = 0.095), and the respondent type (p = 0.377). Sociodemographic factors such as age (p < 0.000), education (p < 0.000), and occupation (p < 0.000) were significantly related to the level of patient satisfaction. We concluded that the majority of respondents are satisfied with the healthcare services provided by RSUZA. Healthcare providers need to focus on the patient’s age, educational level, and occupation in order to increase patient satisfaction, which is a benchmark for the quality of a healthcare service